2011
DOI: 10.3400/avd.cr.10.00005
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Characteristics of a Coronary-pulmonary Artery Fistula with a Coronary Artery Aneurysm

Abstract: Here, we report a case of a 59-year-old woman with a coronary-pulmonary artery fistula with a concomitant coronary artery aneurysm, which comprised an anomalous coronary artery originating at the right coronary cusp, an aberrant branch of the left anterior descending artery, and a coronary artery aneurysm draining into the main pulmonary artery. Histopathologically, non-dilated anomalous coronary artery showed the preservation of internal elastic lamina and medial smooth muscle cell phenotype which lacked in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…(2) Exploring pertinent etiologies is necessary. According to other cases, Degenerated media and smooth muscle layer, suggested by the patient's pathology report, could be attributed to the occurrence of aneurysmal dilatation [19,20].…”
Section: Discussionmentioning
confidence: 75%
“…(2) Exploring pertinent etiologies is necessary. According to other cases, Degenerated media and smooth muscle layer, suggested by the patient's pathology report, could be attributed to the occurrence of aneurysmal dilatation [19,20].…”
Section: Discussionmentioning
confidence: 75%
“…5 Coronary artery fistula can originate from the RCA or the left coronary artery or its branches, but reports show that it most commonly originates from the RCA (55%), with 35% from the left coronary artery and 5% from both coronary arteries. 6 The coronary artery can drain into any cardiac chamber or a large vascular structure. However, the most common site of drainage is the right ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery fistula can originate from the RCA or the left coronary artery or its branches, but reports show that it most commonly originates from the RCA (55%), with 35% from the left coronary artery and 5% from both coronary arteries 6 …”
Section: Discussionmentioning
confidence: 99%
“…These histological findings have not been reported in patients with giant coronary artery aneurysm associated with coronary fistula. However, Sakata, et al 19) suggested that a structural change of the CAF such as disrupted internal elastic lamina and phenotypic changes of the medial smooth muscle cells might contribute to aneurysmal formation (7-8 mm in diameter) in a patient with coronary-pulmonary arterial fistula. Thus, wall weakness related to medial degeneration in addition to a lack of internal and (or) external elastic lamina of the CAF conduit may have contributed to the development of the giant aneurysm in the present patient.…”
Section: Discussionmentioning
confidence: 99%